Biomechanics of elite handcyclists are highly individual—a case series on kinetics, kinematics, and muscular activity - Quittmann, Oliver J.; Birk, Carola; Göll, Fabian; Nolte, Simon; Abel, Thomas (Frontiers in Sports and Active Living, 2025)
AimThis study aimed to assess the biomechanics of handcycling propulsion under various exercise modalities in elite handcyclists with special emphasis on the work distribution between the push and pull phases.MethodsThree elite handcyclists in the H3/4 categories (women = 2) performed several lab tests on their own handbikes that were equipped with a powermeter (P9, SRM GmbH) to detect crank torque at 200 Hz. They performed a submaximal graded exercise test, a ramp test until exhaustion, two sprint tests, and a time-to-exhaustion trial at maximum aerobic power. Crank kinetics and joint kinematics were synchronized with surface electromyography of eight upper-extremity muscles.ResultsThe female athletes relied more on the pull phase, while the male handcyclist seemed to favor the push phase (∼10% more work). Shoulder and elbow flexion were almost unaffected by intensity, whereas other shoulder, wrist, and trunk angles changed individually. Even more differences were found in muscular activation patterns between athletes and they demonstrated high variability in the abdominals. During the time-to-exhaustion, we observed intensified work distributions (for the push and pull phases) and constant patterns. Muscular fatigue was identified in different muscles for the three athletes and covered the descending trapezius, abdominals, and anterior deltoid, respectively.ConclusionThese findings indicate that the biomechanics of handcycling propulsion are highly individual among elite handcyclists and may be influenced by their classification, handbike setup, and muscular capabilities. We encourage future research to replicate this study in a larger cohort and examine how work distributions and other biomechanical parameters change over time to individualize training prescriptions in athletes.